مستوى الاحتراق النفسي لدى المربين في المراكز ذوي الاحتياجات الخاصة - تركي، صفاء (جامعة الوادي university of Eloued, 2019)
الملخص:هدفت هذه الدراسة الى البحث في مستوى الاحتراق النفسي لدى المربين في المراكز ذوي الاحتياجات الخاصة.وذلك على عينة قدرها (31) مربي ومربية في المراكز ذوي الاحتياجات الخاصة التابعة لمدينة الوادي وكذلك مربين من مدرسة الأطفال المعوقين بصريا بالرباح، ومدرسة الأطفال المعوقين سمعيا بالرقيبة. حيث تم اختيارهم بطريقة قصدية عن طريق الخبرة عرضوا على مقياس الاحتراق النفسي لماسلاش وجاكسون (1981). ولقد تم اتباع المنهج الوصفي الاستكشافي، مع استخدام المعالجة الاحصائية spss، والأساليب الاحصائية الفا كرونباخ وجثمان لحساب الخصائص السيكومترية واختبار "ت" لقياس الفرضيات، في حين أن النسب المئوية تم حسابها يدويا، وبعد عرض البيانات ومناقشتها وتحليل وتفسير نتائجها تم استخلاص النتائج التالية: - وجود مستوى منخفض للاحتراق النفسي لدى المربين في المراكز ذوي الاحتياجات الخاصة. - عدم وجود فروق ذات دلالة احصائية في مستوى الاحتراق النفسي لدى المربين في المراكز ذوي الاحتياجات الخاصة تعزى لمتغير الجنس. - عدم وجود فروق ذات دلالة احصائية في مستوى الاحتراق النفسي لدى المربين في المراكز ذوي الاحتياجات الخاصة تعزى لمتغير سنوات الخبرة. - عدم وجود فروق ذات دلالة احصائية في مستوى الاحتراق النفسي لدى المربين في المراكز ذوي الاحتياجات الخاصة تعزى لمتغير الحالة الاجتماعية. - عدم وجود فروق ذات دلالة احصائية في مستوى الاحتراق النفسي لدى المربين في المراكز ذوي الاحتياجات الخاصة تعزى لمتغير طبيعة التكوين. Résumé : This study aims at searching in psychalogical combustion level at the educators in the contr of with special needs. And that on a sample consisting of (31) educators men and women in with special need centre followed to El Oued city and also educators from a school of children who are visually inpaired in Rabbah and a school of children who are hearing inpaired in RGIBA. Where they are chosen with a intentional method dirplayed at psychogical combustion of Maslach and Jackson (1981). And itw as follawed the exploratory and discriptive method. Weth wing the statistical processing (spss). And the statistical manners ALPHA GRONBACH and gotnman for and gotnman for calculating the psychometric properties and testing « t » for measuring the Hypotheses while the percentage was calculated manually ,and after showing the data, discussing them, analysing and clarifying their results, it sorted out the following resuls ; - There isa low psycholical at the educators in with special needs centre. - there are no differences of statistical significance in sphycological combustion level at the educators in with special needs centre attributed to sexy variable. - There are no differeces of statistical significance in sphycological combustion level at the educators in with special needs centre attributed to experience years variable. - There are no differeces of statistical significance in sphycological combustion level at the educators in with special needs centre attributed to social situation variable. - There are no differeces of statistical significance in sphycological combustion level at the educators in with special needs centre attributed to formation nature variable.
دراسة وصفية استكشافية في المراكز النفسية البيداغوجية والمؤسسات ذوي الاحتياجات الخاصة بولاية الوادي
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: الإحتراق النفسي، المربي; Épuisement psychologique, éducatrice; Psychological burnout, educator